Avaliação do potencial farmacológico de derivados semissintéticos de terpenos obtidos do óleo de copaíba (Copaifera spp.- Fabaceae) - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Copaiba oil from several species of the genus copaifera has been used for many years, commercially, because of its possible modulatory action on inflammatory processes. Phytochemical studies of the species, which elucidate their chemical composition, fractionated in sesquiterpenes and diterpenes, have been performed. Although crude oil is well studied, it is scarce to know the effect of its isolated substances, and there are few studies on the structural modifications of these diterpene acids, seeking to improve their biological activities. In this sense, the present work had as objectives the isolation of the majority diterpenic acids present in the Copaifera multijuga oil: copalic and 3-hydroxy-copalic acids and Copaifera reticulata: hardwickiic acid, with structural modifications in the 2 (two) lowcost and optimized chemistries, as well as in vitro and in vivo assays of the substance with the best anti-inflammatory screening and subsequent in silico studies. After isolation, the substances were semi-synthesized and their structures elucidated by 1H and 13C NMR analysis, and therefore, tested in cell viability assay and TNF-α inhibition activity check test in vitro. The in vivo model of pleurisy/pleuritis in balb-c mice was performed with the best anti-inflammatory substance (ACD13B-esterification of ibuprofen with 3-hydroxy-copalic acid), as well as expression assay of IKB-α protein. In addition, the gastrointestinal test was also performed with the same substance. The semi-synthesized derivatives were: ACD4- epoxidation of copalic acid, ACD13B-esterification of ibuprofen with 3-hydroxy-copalic acid and ACD51-acylation of phthalic anhydride with 3-hydroxy-copalic acid. ACD13B showed no cytotoxic potential in the THP-1 line when tested at the concentration of 2 μM. The other substances did not present significant cytotoxicity at concentrations tested. In addition, ACD13B significantly inhibited TNF-α production in LPS-stimulated THP-1 cells. In animals with induced pleurisy, ACD13B reduced the total number of leukocytes by 40% and the number of mononuclear cells at a dose of 100 mg/kg intraperitoneally (IP) by up to 50%. There was also inhibition of pIKB-α. ACD13B presented a lower gastrointestinal effect when compared to ibuprofen in mice. The docking study revealed the affinity and mode of interaction of the substance ACD13B in COX-2 and COX-1, identifying hydrophobic and hydrophilic interactions. The results indicate that the ibuprofen derivative with 3-hydroxy copalic acid is a prototype of an anti-inflammatory drug with a lower gastrointestinal effect than ibuprofen, which may be explored in the future for other functional and therapeutic properties.
Keywords: Copaíba; Diterpenos; Agentes antiinflamatórios - Derivados; CIÊNCIAS DA SAÚDE: FARMÁCIA; Copaíba (Copaifera L.); Diterpenos; Docking; Modificação estrutural; Antiinflamatório; Derivado; Ibuprofeno; Pleurisia